Thermoactivation spectroscopy of solid Ar doped with N₂ - Ponomaryov, A.N.; Savchenko, E.V.; Gumenchuk, G.B.; Khizhniy, I.V.; Frankowski, M.; Bondybey, V.E. (Физика низких температур, 2007)
A new modification of low-temperature activation spectroscopy technique for real-time correlated study
of relaxation processes in cryogenic solids was developed. This enabled us to measure simultaneously thermally
stimulated exoelectron emission (TSEE) and spectrally resolved thermally stimulated luminescence
(TSL) in the range from 200 to 1100 nm. This paper presents the results on TSL and TSEE from solid Ar
doped with N₂ exposed to irradiation by low-energy electron beam (500 eV) during deposition. The TSEE
and TSL yields were measured at the heating rate of 3.2 K/min. The emissions of molecular (A³Σu⁺ → X¹Σg⁺ transition) and atomic (²D → ⁴S transition) nitrogen in the TSL spectra and their temperature behavior were
studied. Drastic changes in the intensity distribution of the molecular progression were observed with temperature
rise. In low-temperature range «hot» vibrationally unrelaxed transitions were detected in contrast
to «cold» vibrationally relaxed transitions observed in «high» temperature TSL. The mechanisms of the processes
resulting in TSL in whole temperature range of Ar solid occurrence are suggested.